Pengaruh Model Pembelajaran Discovery Learning dan Keterampilan Berpikir Kreatif Terhadap Pemahaman Konsep Biologi Siswa SMA Bunda Hati Kudus - Putranti, Candarasmi Dwi; Ghoghi, Ferdinandus FR (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In the era of globalization marked by the presence of Society 5.0, education faces new challenges. One of the essential skills that students need to have is critical thinking. The discovery learning learning model is considered effective in fostering students' critical thinking skills, so that it can improve their understanding of concepts. This study aims to determine the influence of the discovery learning model and creative thinking skills on the understanding of biology concepts of SMA Bunda Hati Kudus students. The research method used is a quantitative method. The population of this study used 160 students in class XI science of Bunda Hati Kudus High School for the 2022/2023 school year. The sample used was 64 people. Hypothesis testing using MANOVA and ANOVA techniques with a significance level of 0.05. The results of the study show that the application of the discovery learning learning model significantly improves the understanding of concepts, critical thinking skills, and creative thinking skills of SMA Bunda Hati Kudus students. Statistical analysis with the F test showed a very significant difference (p < 0.05) between the group of students who used the discovery learning model and the group that used the direct learning model. These findings indicate that the discovery learning model can be an effective alternative to improve the quality of student learning